EFEKTIVITAS PERUMDA AGRO SUKABUMI MANDIRI DALAM UPAYA PEMBANGUNAN DI KABUPATEN SUKABUMI - Wida Ibrahim; Anna Fitria Agustina (Mimbar Administrasi Mandiri, 2024)
The lack of public knowledge about the function of Perumda ASM in improving the development of Sukabumi Regency, the vast land area of Sukabumi Regency which has the potential to be managed by its natural resources makes Perumda ASM unable to work as a whole, the role of Perumda ASM in improving development in Sukabumi Regency has not been effective because it was recently established so that there has not been a match in the amount of revenue, the timeliness of revenue that has not been appropriate because Perumda ASM has only been operating, and the quality of human resources managers is not optimal. These problems can be seen from the theory used, namely Hidayat's theory with 3 dimensions of research, namely quality, quantity and time. The approach used by researchers is qualitative with descriptive methods, data collection techniques using interview techniques, observation, and documentation and applying triangulation techniques. Then analyze the data using data reduction, data presentation, and conclusion drawing. The informants in this study amounted to 6 people, using purposive sampling and snowball sampling techniques. These informants are the President Director of Perumda Agro Sukabumi Mandiri, Head of General and Personnel, Head of Planning and Evaluation, Planning and Evaluation Staff, Agribusiness Actors, and the Community. The results showed that the effectiveness of Perumda Agro Sukabumi Mandiri in development efforts in Sukabumi District has not gone well. This can be seen from the quality of potential and public understanding of the role of Perumda ASM is not good, the quantity of achievement targets and the suitability of the amount of revenue is not appropriate, the accuracy of revenue and reporting is not appropriate. The conclusion of this study is that because the indicators of each are not yet appropriate, the Effectiveness of Perumda Agro Sukabumi Mandiri in Development Efforts in Sukabumi District has not been achieved.